Perancangan Sistem Informasi Rekomendasi dan Pengelolaan Kegiatan Literasi Buku Menggunakan Algoritma Decision Tree Berbasis Web: Studi Kasus: Yayasan Perguruan Ira - Afifah Aqila Nasution; Niko Surya Atmaja; Rico Imanta Ginting (Jurnal Ilmiah Teknik Mesin, Elektro dan Komputer, 2026)
The Library of Yayasan Perguruan IRA has a collection of 8,885 books divided into nine categories. However, its management is still carried out in a simple manner, causing the process of searching for book information to take a long time, library services to be less optimal, and literacy activities to not yet utilize collection data as a basis for planning. This study aims to design a web-based library book collection information system integrated with the Decision Tree algorithm to generate literacy activity recommendations that are suitable for the condition of the available book collections. The program is developed using a web-based approach with a relational database for structured data storage, while the Decision Tree algorithm is applied to classify collection patterns and produce appropriate literacy recommendations. The program design results show that book information searches can be performed more quickly, collection data can be stored in a structured and easily accessible manner, and literacy activity recommendations can be generated based on collection data analysis using an algorithm. Compared to the currently running management program, the web-based program offers more efficient data management, faster information searches, and data-driven literacy planning. The implementation of this program is expected to improve the effectiveness of library management and support the development of literacy programs at Yayasan Perguruan IRA